Hybrid International Comparative Group Work on Digitalization in Adult Education and Learning - Emmanuel Jean-Francois; Therese Rosemann; Rehana Saleem Panjwani; Funmilayo Adewole (AS: Andragoška Spoznanja)
This study aimed to analyse the experiences of two moderators and two participants in an International Comparative Group Work on Digitalization in Adult Education and Learning, which was organised through a hybrid mode of delivery, to provide intercultural perspectives that can inform the understanding of instructional designers and adult educators, as well as other practitioners involved in the digitalization of adult education. Hybrid learning and intercultural learning theory informed the conceptual framework of this study. This is a qualitative research study, which used collaborative autoethnography as the methodology for the overall inquiry. The researchers used their autobiographical stories to analyse their lived experiences throughout their journey interacting in the international comparative group work. The results show that design features related to the planning and implementation of the hybrid international comparative group work on digitalization in adult education and learning enabled the moderators and the participants to experience intercultural learning.